DILG Negros Occidental Contact Tracer Information Management System - Reguindin, John Christopher; Sabay, Reymund; Madrigal, Dennis (Technium BioChemMed, 2021)
COVID-19 pandemic reshapes the use of technology and innovation in an organization. Organizations are adopting and utilizing technologies in their day-to-day operations. Information Systems offer a wide range of solutions in terms of data management and interconnecting people with the use of a system. Its use was proven to enhance and improve the productivity of an organization in this pandemic. These promising results led the researcher to develop the Department of the Interior and Local Government (DILG) Negros Occidental Contact Tracer Information Management System (CTIMS). The CTIMS is a web application that enables DILG Negros Occidental Personnel to manage and facilitate all DILG Hired-Contact Tracers (CT) in the Province of Negros Occidental. The automated system made the data collection easy and error-free, streamlined reporting, and eliminated the time-consuming process of consolidating the Accomplishment Reports (ARs) from the Field and Provincial Offices. The document tracker feature replaced the manual entry in the logbook. It also improved the received and released document reporting. It improved the processes of the CT Task team compared to the manual operations and is expected to increase the productivity, effectivity, and efficiency of DILG Negros Occidental.